2007
DOI: 10.1136/bmj.39070.573032.80
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of insulating existing houses on health inequality: cluster randomised study in the community

Abstract: Objective To determine whether insulating existing houses increases indoor temperatures and improves occupants' health and wellbeing.Design Community based, cluster, single blinded randomised study.Setting Seven low income communities in New Zealand.Participants 1350 households containing 4407 participants.Intervention Installation of a standard retrofit insulation package.Main outcome measures Indoor temperature and relative humidity, energy consumption, self reported health, wheezing, days off school and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
313
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(331 citation statements)
references
References 17 publications
14
313
0
4
Order By: Relevance
“…Studies from New Zealand reported improved comfort, indoor air quality (IAQ), and health symptoms resulting from upgrading insulation and replacing ineffective heating systems or heating systems that vent combustion gases to indoors [8,9]. Because pre-retrofit indoor air temperatures were lower than typical temperatures in U.S. homes and because many of the New Zealand homes had heating systems that vented combustion gases indoors, the results of this study are not generally applicable to U.S. homes.…”
Section: Introductionmentioning
confidence: 46%
“…Studies from New Zealand reported improved comfort, indoor air quality (IAQ), and health symptoms resulting from upgrading insulation and replacing ineffective heating systems or heating systems that vent combustion gases to indoors [8,9]. Because pre-retrofit indoor air temperatures were lower than typical temperatures in U.S. homes and because many of the New Zealand homes had heating systems that vented combustion gases indoors, the results of this study are not generally applicable to U.S. homes.…”
Section: Introductionmentioning
confidence: 46%
“…These were pre-post comparisons only, rather than temperature changes relative to control households, but were controlled for external conditions. Howden-Chapman et al (2007) found increases in average bedroom temperatures of 0.50 K and decreases in average relative humidity levels of 2.3% RH (Howden-Chapman et al, 2007). The Glasgow Warm Homes Study (Caldwell et al, 2001) found increases in mean temperatures of more than 2 K for the living room and 3 K for the bedroom.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that both insulation and heating measures can increase living room and bedroom temperatures (Caldwell et al, 2001;Howden-Chapman et al, 2007;. Evidence further suggests that energy-efficiency improvements can lower indoor relative humidity levels in both living rooms and bedrooms, and that these effects are greater for more extensive improvements .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Watcombe housing study conducted in the UK (Barton et al, 2007) investigated self-reported asthma rates in households with improved heating and insulation and found a statistically significant but negligible effect on asthma prevalence. Two prominent randomized controlled studies in NZ looked at the effects of housing improvement on respiratory conditions in general (Howden-Chapman et al, 2007) and asthma specifically (HowdenChapman et al, 2008) and found beneficial causal effects. Crane et al (1998) investigated the effect of installing a Mechanical Ventilation Heat Exchange system on the presence of HDM in NZ homes and found no significant effects.…”
Section: Introductionmentioning
confidence: 99%